Pattern recognition : 38th German Conference, GCPR 2016, Hannover, Germany, September 12-15, 2016, Proceedings /: 38th German Conference, GCPR 2016, Hannover, Germany, September 12-15, 2016, Proceedings. (2016) - Unknown
No abstract available